Monitoring Drug Safety Information - Recommendations of Foreign Regulatory Authorities - Elena V. Shubnikova; Marya A. Darmostukova; Irina I. Snegireva; Evgeniya O. Zhuravleva (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2020)
Analysis of administrative decisions of foreign regulatory authorities on the recoil of medicines and/or the need for changes in the instructions for their medical use due to changes in the safety proﬁ le, conducted by experts of the Scientiﬁ c Centre for Expert Evaluation of Medicinal Products revealed 16 administrative decisions. These decisions contained information on the following medicines registered in Russia: norepinephrine, xylometazoline, mometason, liraglutide recombinant, exenatide, insulin recombinant human, insulin degludec, teriparatide, progesterone, gestodene, desogestrel, dienogest, drospirenone, norgestrel, lynestrenol, levonorgestrel, medroxyprogesterone, mestranol, nomegestrol, norethisterone, norgestimate, chlormadinone, cyproterone, estradiol, ethinylestradiol, etonogestrel, ethinylestradiol, ﬁ nasteride, abiraterone, thiamazole, omega-3-acid ethyl esters, pitavastatin.